Food pantry assistance and the great recession. Issue 1 (4th March 2019) - Heflin, Colleen; Price, Ashley
ABSTRACT: Using nationally representative data from the National Center for Charitable Statistics and the Current Population Survey Food Security Supplement, this study documents trends in the supply of and demand for food pantry assistance. While the number of food pantries has grown dramatically since 1995, there has been little expansion since the end of the Great Recession, a period of worldwide economic downturn that occurred between December 2007 and June 2009 in the United States, despite an increase in the number of households that report receiving food from food pantries. In the last 10 years, those who participate in food pantries have become older, more likely to have some college education, be divorced, separated or widowed, and unemployed after the Great Recession. Finally, we document that personal demographic characteristics associated with pantry use closely follow the correlates of poverty itself.